Comparative studies of localized buckling in sandwich struts with different core bending models - Wadee, M. Ahmer; Theofanous, Marios; Yiatros, Stylianos (My University, 2010)
Analytical models with geometric non-linearities accounting for interactions between local and global instability modes leading to localized buckling in sandwich struts are formulated. For the core material response, two increasingly sophisticated bending models are compared against each other: Timoshenko beam theory (TBT) and Reddy–Bickford beam theory (RBT). Numerical solutions of the analytical models are validated with the commercial finite element code ABAQUS. It is found that there is a small but significant difference in the critical load between the two models and that the previously obtained solution slightly underestimates the linear buckling strength. More importantly, it is found that the RBT model predicts the onset of interactive buckling before the TBT model and, according to the results from the finite element study, matches the actual behaviour of a strut in both its initial and advanced postbuckling states with excellent correlation.
Keywords: Structural stability; Bifurcation; Interactive buckling; Localization; Shear deformation; Composite structures